Effectiveness and implementation of enhanced recovery after surgery programmes: a rapid evidence synthesis. Issue 7 (22nd July 2014) - Paton, Fiona; Chambers, Duncan; Wilson, Paul; Eastwood, Alison; Craig, Dawn; Fox, Dave; Jayne, David; McGinnes, Erika
Abstract : Objectives: To assess the evidence on the impact of enhanced recovery programmes for patients undergoing elective surgery in acute hospital settings in the UK. Design: Rapid evidence synthesis. Eight databases were searched from 1990 to March 2013 without language restrictions. Relevant reports and guidelines, websites and reference lists of retrieved articles were scanned to identify additional studies. Systematic reviews, RCTs not included in the systematic reviews, economic evaluations and UK NHS cost analysis, implementation case studies and surveys of patient experience in a UK setting were eligible for inclusion. Primary and secondary outcome measures: We assessed the impact of enhanced recovery programmes on health or cost-related outcomes, and assessed implementation case studies and patient experience in UK settings. Studies were quality assessed where appropriate using the Centre for Reviews and Dissemination Database of Abstracts of Reviews of Effects critical appraisal process. Results: 17 systematic reviews and 12 additional RCTs were included. Ten relevant economic evaluations were included. No cost analysis studies were identified. Most of the evidence focused on colorectal surgery. 14 innovation case studies and 15 implementation case studies undertaken in National Health Service settings described factors critical to the success of an enhanced recovery programme. Evidence for colorectal surgery suggests that enhanced recovery programmes may reduce hospital stays by 0.5–3.5 days compared with conventional care. There were no significant differences in reported readmission rates. Other surgical specialties showed greater variation in reductions in length of stay reflecting the limited evidence identified. Findings relating to other outcomes were hampered by a lack of robust evidence and poor reporting. Conclusions: There is consistent, albeit limited, evidence that enhanced recovery programmes can reduce length of patient hospital stay without increasing readmission rates. The extent to which managers and clinicians considering implementing enhanced recovery programmes in UK settings can realise savings will depend on length of stay achieved under their existing care pathway.